PENGARUH DISIPLIN KERJA, MOTIVASI, IKLIM ORGANISASI, KOMPENSASI TERHADAP KINERJA (Survei pada karyawan non fungsional RSUD Dr. Harjono S Kabupaten Ponorogo) - ð’ð®ð¤ð¨ð°ðšðð¢, ðƒð¢ð²ðšð¡; ð’ð®ððð¢ð§, ð€ð¥ð°ð¢; ð’ð®ððšð«ð§ð¨, ð’ð®ððšð«ð§ð¨ (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purpose of this study was to determine the significance of the influence of work discipline, motivation, organization climate, compensation on performance. of non fungsional employees at the Regional General Hospital (RSUD) Dr. Harjono S Ponorogo Regency.Data collection in the form of answers to the questionnaire as primary data and documentation as secondary data. The number of research samples were 55 non-functional employees with a sampling method using saturated sampling. Data analysis methods used are validity and reliability test, classic assumption test, hypothesis test, F test, and coefficient of determination test.Regression calculation results show that motivation and discipline have a significant effect on the performance of nurses at Dr. Harjono S Hospital, Ponorogo district. This is indicated by the significant probability value of each variable < 0,05. While the compensation and organizational climate have no significant effect on the performance of nurses at Dr. Harjono S Ponorogo Regency. This is indicated by the significant probability value > 0,05.